2015
DOI: 10.5194/gmd-8-2701-2015
|View full text |Cite
|
Sign up to set email alerts
|

Using field observations to inform thermal hydrology models of permafrost dynamics with ATS (v0.83)

Abstract: Abstract. Climate change is profoundly transforming the carbon-rich Arctic tundra landscape, potentially moving it from a carbon sink to a carbon source by increasing the thickness of soil that thaws on a seasonal basis. However, the modeling capability and precise parameterizations of the physical characteristics needed to estimate projected active layer thickness (ALT) are limited in Earth system models (ESMs). In particular, discrepancies in spatial scale between field measurements and Earth system models c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
170
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(174 citation statements)
references
References 78 publications
(121 reference statements)
3
170
1
Order By: Relevance
“…Three recent studies have used other mechanistic models to simulate soil temperature fields at this site and achieved comparably good comparisons with observations (Kumar et al, 2016 applied a 3-D version of PFLOTRAN; Atchley et al, 2015 andHarp et al, 2016 applied a 1-D version of the Arctic Terrestrial Simulator -ATS). However, those models used measured soil temperatures near the surface as the top boundary condition.…”
Section: Soil Temperature and Active Layer Depthmentioning
confidence: 94%
“…Three recent studies have used other mechanistic models to simulate soil temperature fields at this site and achieved comparably good comparisons with observations (Kumar et al, 2016 applied a 3-D version of PFLOTRAN; Atchley et al, 2015 andHarp et al, 2016 applied a 1-D version of the Arctic Terrestrial Simulator -ATS). However, those models used measured soil temperatures near the surface as the top boundary condition.…”
Section: Soil Temperature and Active Layer Depthmentioning
confidence: 94%
“…Atchley et al (2015) and Harp et al (2016) have successfully demonstrated the use of such techniques for three-phase hydrology models at one of our sites (site C) and would inform our future studies.…”
Section: Why Not To Calibratementioning
confidence: 99%
“…Figure 3 illustrates the subsurface soil horizons based on observations that we used in all our modeling studies presented here. In absence of colocated observations for soil hydraulic and thermal properties we derived the data for use in our studies from the published literature in tundra regions (Hinzman et al, 1991(Hinzman et al, , 1998) and a recent parameter calibration study conducted at one of our sites (Site C) (Atchley et al, 2015). Table D1 shows the soil hydraulic and thermal properties used in our modeling study.…”
Section: Subsurface Characterizationmentioning
confidence: 99%
“…Thus the flow velocity is variable in three dimensions: Vertical variations in the velocity are caused not only by variations in porosity and permeability over depth (Quinton et al, 2008), humification (Letts et al, 2000) and diplotelmic flow (Jessen et al, 2014) but are also related to the existence of a saturated layer at the bottom of the active layer. Lateral alterations of the velocity arise due to a network of water paths that is controlled by the micro-topography of the permafrost table (Atchley et al, 2015). 5…”
Section: Solute Transport In the Active Layermentioning
confidence: 99%
“…The microtopograhpy of the frost table creates a complicated flow networks that also lead to lateral flow (Atchley et al, 2015). Models capable of simulating the complex mechanisms occurring in cold climate environment have only recently emerged (Kurylyk et al, 2014) and are still 15 under development.…”
Section: Introductionmentioning
confidence: 99%